Eye Contact Judgment Is Influenced by Perceivers’ Social Anxiety But Not by Their Affective State - Chen, Tingji; Nummenmaa, Lauri; Hietanen, Jari K. (Frontiers in Psychology, 2017)
Fast and accurate judgment of whether another person is making eye contact or not is crucial for our social interaction. As affective states have been shown to influence social perceptions and judgments, we investigated the influence of observers’ own affective states and trait anxiety on their eye contact judgments. In two experiments, participants were required to judge whether animated faces (Experiment 1) and real faces (Experiment 2) with varying gaze angles were looking at them or not. Participants performed the task in pleasant, neutral, and unpleasant odor conditions. The results from two experiments showed that eye contact judgments were not modulated by observers’ affective state, yet participants with higher levels of social anxiety accepted a wider range of gaze deviations from the direct gaze as eye contact. We conclude that gaze direction judgments depend on individual differences in affective predispositions, yet they are not amenable to situational affective influences.